The SPECIFICUL INTEGRĂRII ECONOMICE ÎN REGIUNEA BALCANICĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
The liberalization of commerce has become one of the principal instrument in promoting the regional cooperation in South-Eastern Europe. The liberalization of commerce in SEE has become an important goal of the EU the from political and economic point of view. As a regional and important criterion for the EU at the individual evaluation of SEE countries, the implementation of certain measures will assure a faster integration in the EU. The process of liberalization of commerce between SEE and the EU was implemented asymmetrically, specially by a larger opening of the EU market the SEE markets.